1999
DOI: 10.1111/j.1939-1676.1999.tb01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Clinical Utility of Ambulatory Electrocardiographic (Holter) Recordings in Syncopal Dogs: 44 Cases (1991–1995)

Abstract: The objective of this study was to evaluate retrospectively the clinical utility of ambulatory (Holter) electrocardiographic monitoring in syncopal dogs and to compare the Holter recording with the clinic electrocardiogram (ECG) in these animals. Fifty Holter reports and 44 medical records from 44 dogs were evaluated. A syncopcal episode occurred during monitoring in 24% of the recordings. No obvious relationship was found between the frequency of syncope occurring before Holter recording and the likelihood of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…This is reflected in the lack of fixed or proportional bias between the in‐clinic ECG HR and the 1st h Holter HR – a period during which the dog is in an anxious state. A similar discrepancy in HR measurements between ECG and 24‐hour Holter have been observed previously in dogs with sinus rhythm and syncope of various aetiologies, but excluding AF (Miller et al ), in healthy dogs predisposed to myxomatous mitral valve disease (MMVD) (Rasmussen et al ) and in dogs with MMVD (Crosara et al ). Crosara et al () found a significantly greater difference between HR recorded by in‐clinic ECG as compared to an average HR recorded by 24‐hour Holter in dogs with subclinical heart disease.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This is reflected in the lack of fixed or proportional bias between the in‐clinic ECG HR and the 1st h Holter HR – a period during which the dog is in an anxious state. A similar discrepancy in HR measurements between ECG and 24‐hour Holter have been observed previously in dogs with sinus rhythm and syncope of various aetiologies, but excluding AF (Miller et al ), in healthy dogs predisposed to myxomatous mitral valve disease (MMVD) (Rasmussen et al ) and in dogs with MMVD (Crosara et al ). Crosara et al () found a significantly greater difference between HR recorded by in‐clinic ECG as compared to an average HR recorded by 24‐hour Holter in dogs with subclinical heart disease.…”
Section: Discussionsupporting
confidence: 77%
“…This might inadequately reflect the average HR because of adrenergic stimulation resulting in increased HR. Indeed, auscultated or ECG‐derived HR in healthy and diseased dogs in sinus rhythm are significantly higher than 24‐hour Holter–derived average HR (Marino et al , Miller et al , Crosara et al , Rasmussen et al , Oliveria et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Ventricular premature contractions are a common finding in Doberman Pinschers with cardiomyopathy and may lead to sudden cardiac death in 25–30% of the cases in the occult phase of the disease 3,7,8,16,17 . Because of the high frequency of electrical abnormalities in this breed, Holter examination was suggested to be the best test for detecting early changes, 3,7,17 and thus Holter examinations have been evaluated and recommended in Doberman Pinschers as well as in other breeds for the purpose of diagnostic and therapeutic considerations 3,7,17,19–25 . However, availability of Holter recorders and expense of this technique may preclude its use in many dogs 18,26 .…”
Section: Discussionmentioning
confidence: 99%
“…A diagnostic advantage with prolonged duration of monitoring for detection of arrhythmia events has been reported for Holter/event monitors (Miller et al . , Bright et al , Wess et al . ) and for wireless devices (Lobodzinski , Rosenberg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Excessive motion artefacts are also common in ECG monitoring with Holter and event monitors, which are currently used for long‐term monitoring in veterinary medicine (Miller et al . , Bright et al ). Another problem was the difficulty in firmly attaching the self‐adhesive electrodes.…”
Section: Discussionmentioning
confidence: 99%